An Analysis of Webtoon Application Usage as a Learning Medium in Reading Comprehension Skills of 11th Grade Students at SMA Negeri 6 Bengkulu Tengah - Sari, Intan Permata; Riswanto, Riswanto; Haryanto, Endang (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the use of the Webtoon application as a learning medium and to examine students’ perceptions of its use in reading comprehension skills of eleventh-grade students at SMA Negeri 6 Bengkulu Tengah. This research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research subjects included one English teacher and eight eleventh-grade students who were selected through purposive sampling. The findings indicate that the use of the Webtoon application as a reading learning medium has a positive impact on students’ reading comprehension skills. Webtoon can increase students’ interest, motivation, and engagement in the learning process. Visual support in the form of images, character expressions, and storylines helps students understand the reading content, identify main ideas, comprehend new vocabulary, and follow the storyline coherently. In addition, students showed very positive perceptions of the use of Webtoon because the learning activities became more interesting, enjoyable, and less monotonous. However, this study also identified several challenges in using Webtoon as a learning medium. These challenges include limited internet access, which occasionally disrupted students’ ability to access the application; limited storage capacity on students’ devices, which prevented some students from installing the application; and students’ tendency to focus more on visual elements than on the reading text itself. Nevertheless, these challenges did not significantly hinder the learning process, as they could be addressed through clear instructions, continuous guidance, and effective classroom management by the teacher. Therefore, it can be concluded that the Webtoon application is an effective, relevant, and practical learning medium to support students’ reading comprehension skills at the secondary school level.